Answer:
The second choice is the correct one
Step-by-step explanation:
(2x+3)^2 + 8(2x+3) + 11 = 0
To use the u substitution, we will assume that:
2x + 3 = u
Substitute with this in the given expression, we will get:
u^2 + 8u + 11 = 0
The general form of the second degree equation is:
ax^2 + bx + c = 0
Comparing the expression we reached with the general one, we will find that:
a = 1
b = 8
c = 11
The roots can be found using the rule found in the attached picture.
This means that, for the given expression:
u = -4 ± √5
Now, we have:
u = 2x+3
This means that:
at u = -4 + √5
2x + 3 = -4 + √5
2x = -7 + √5
x = (-7 + √5) / 2
at u = -4 - √5
2x + 3 = -4 - √5
2x = -7 - √5
x = (-7 - √5) / 2
This means that, for the given expression:
x = (-7 ± √5 ) / 2
Hope this helps :)